Brain power : understanding human intelligence - Haines, Gail Kay (An Impact book, 1979)
Explores the human mind, focusing on our understanding of "intelligence" and discussing how learning occurs, how intelligence is measured, what creativity is, and current developments in brain research and its possible applications.